2014
DOI: 10.1155/2014/120686
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nocturnal Enuresis and Its Associated Factors in Primary School and Preschool Children of Khorramabad in 2013

Abstract: Background. Nocturnal enuresis refers to an inability to control urination during sleep. This study aimed to determine the prevalence of nocturnal enuresis and its associated factors in children in the city of Khorramabad. Materials and Methods. In this descriptive-analytic, cross-sectional study, 710 male and female children were divided into two groups with equal numbers. The samples were selected from the schools of Khorramabad using the multistage cluster and stratified random sampling methods based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
29
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 29 publications
10
29
1
6
Order By: Relevance
“…So the family history of NE seems to be correlated with higher parental intolerance and higher rate of punishment [21]. According to the same study, punishment was observed more frequently in girls than in boys (20 of 35 or 57.1% vs. 4 of 20 or 20%), which was different from the observation of another study based on the fact that the prevalence of punishment is higher among boys [22]. …”
Section: Discussionmentioning
confidence: 99%
“…So the family history of NE seems to be correlated with higher parental intolerance and higher rate of punishment [21]. According to the same study, punishment was observed more frequently in girls than in boys (20 of 35 or 57.1% vs. 4 of 20 or 20%), which was different from the observation of another study based on the fact that the prevalence of punishment is higher among boys [22]. …”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire was designed for this study after examining previous studies on MNE [6][7][8]. After obtaining approval of the local ethical committees of Sohag University Hospital, Qena University Hospital, and the concerned education authorities in both governorates, the questionnaire was first presented to a small sample of 100 students to test its validity.…”
Section: Questionnairementioning
confidence: 99%
“…Farklı ülkelerden 6-11 yaş grubunda enürezis sıklığı %1,4 ile 28 arasında rapor edilmiştir (13)(14)(15). Ülkemizdeki sıklık diğer bölgelerde %12,5 ile 17 arasında bildirilirken Güneydoğu Anadolu bölgesinde sıklığın %25'lere kadar çıktığı tespit edilmiştir (2,4,16).…”
Section: Discussionunclassified
“…Epidemiyolojik çalışmaların önemli bir kısmında annenin düşük eğitim düzeyi ile enürezis noktürna arasında anlamlı ilişki saptanmıştır (3,4,13). Yüksek eğitim düzeyi ile ilişkili bulunan bazı yayınlara karşın, eğitim düzeyi ile anlamlı ilişki olmadığını gösteren yayınlar da mevcuttur (6,14). Çalışmamızda olguların %65'inde annelerin eğitim düzeyinin düşük olduğu gözlendi.…”
Section: Discussionunclassified